Adsorption of methylene blue dye by calix6arene-modified lead sulphide PbS: optimisation using response surface methodology - Rosly, Nor Zida; Abdullah, Abdul Halim; Ahmad Kamarudin, Mazliana; Ashari, Siti Efliza; Alang Ahmad, Shahrul Ainliah (Multidisciplinary Digital Publishing Institute, 2021)
Lead sulphide (PbS) modified with calix[6]arene was synthesised as an alternative and regenerative adsorbent for the adsorption of methylene blue (MB) dye. The prepared calix[6]arene-modified PbS was characterised via Fourier-transform infrared spectroscopy, field emission scanning electron microscopy, and energy-dispersive X-ray spectroscopy. The response surface methodology (RSM) based on the central composite design (CCD) was employed to identify the most significant factors, such as the initial concentration, adsorbent dosage, pH, and temperature, and to optimise the effects of the factors on the adsorptive efficiency as its response. The optimised initial concentration, adsorbent dosage, pH, and temperature were 20.00 mg/L initial concentration, 44.00 mg calix[6]arene-modified PbS, pH 6, and a temperature of 31.00 °C. A good correlation between the values and well-fitted model was observed. The adsorption performance was evaluated based on the percentage removal of MB dye from the water system. The adsorption isotherm best fit the Langmuir isotherm model, and the adsorption rate was followed by a pseudo-second-order kinetic model, a single layer chemical adsorption with a maximum adsorption capacity (qmax) of 5.495 mg/g.